Association between health literacy and the time to first cigarette among daily smokers in Zhejiang Province, China - Hu, Xiujing; Yao, Dingming; Chen, Heni; Lv, Qiaohong; Yan, Xiaotong; Zhao, Yusui; Zhang, Xuehai; Xu, Yue (Frontiers in Public Health, 2025)
BackgroundNicotine dependence significantly impedes smoking cessation efforts, yet limited research has explored its relationship with health literacy in the Chinese context. This study aimed to investigate the association between health literacy and nicotine dependence among daily smokers in Zhejiang Province, China, with particular focus on potential threshold effects.MethodsWe conducted a cross-sectional study involving 3,235 daily smokers (99.23% male) from the 2022 Chinese Health Literacy Survey in Zhejiang Province. Health literacy was assessed using a validated Chinese health literacy scale (0–66 points), while nicotine dependence was measured by time to first cigarette (TTFC ≤ 30 min indicating high dependence). Multivariable logistic regression and threshold effect analysis were conducted to examine the relationship between health literacy levels and nicotine dependence.ResultsHealth literacy was significantly inversely associated with high nicotine dependence across all models (fully-adjusted OR = 0.99 per point increase, 95%CI: 0.98–0.99, p < 0.001). A clear threshold effect was observed at 53 points (the standard for adequate health literacy), with individuals scoring ≥53 having 34% lower odds of high nicotine dependence compared to those with below basic literacy (OR = 0.66, 95%CI: 0.50–0.87, p = 0.003). A significant dose–response relationship was evident across health literacy categories (P for trend <0.001), with protective effects emerging at intermediate literacy levels (40 52 points) and strengthening at adequate levels (53 66 points).ConclusionHealth literacy exhibits an independent, protective association against nicotine dependence among daily smokers in this predominantly male sample, with effects becoming pronounced above the adequacy threshold. These findings suggest that integrating tobacco control objectives within China’s existing health literacy promotion framework may enhance smoking cessation efforts and reduce nicotine dependence, particularly in regions like Zhejiang Province that continue to face high male smoking prevalence despite active tobacco control policies.